The role of policy actors’ belief systems and interests in framing public health nutrition problems: a case study of obesity in Australia - Patricia Ribeiro de Melo; Phillip Baker; Priscila Pereira Machado; Elly Howse; Tanita Northcott; Mark Lawrence (Public Health Nutrition)
Abstract